2014
DOI: 10.1007/s12031-014-0386-4
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Amygdalar AMPAergic/GABAergic Mechanisms Promote Anxiolitic-Like Effects in an Unpredictable Stress Model of the Hamster

Abstract: Studies have pointed to both α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptor (AMPAR) antagonists and GABA(A) receptor (GABA(A)R) agonists as potent antistress agents. In this work, separate subchronic injections of the AMPAR antagonist, 6-ciano-7-nitroquinoxaline-2,3-dione (CNQX), and α1 GABA(A)R subunit agonist (Zol) within the central amygdala nucleus modified the elevated plus maze performances of hamsters exposed randomly to one of the following stressful conditions: food/water deprivation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…Some animal experiments have indicated that administration of GABA receptor agonists or antagonists into the amygdala can influence the concentration of GABA ( Sanders and Shekhar, 1995 ; Barbalho et al, 2009 ). These have included GABAergic agonists such as benzodiazepines ( Sigel and Lüscher, 2011 ), Zol ( Alò et al, 2015 ), muscimol ( Jasnow and Huhman, 2001 ; Liu et al, 2009 ), diazepam, and abecarnil ( Eva et al, 2004 ). GABAergic antagonists have included baclofen ( Gorsane et al, 2012 ), bicuculline ( Liu et al, 2009 ), and FG-7124 ( Eva et al, 2004 ; Lukkes et al, 2012 ).…”
Section: Gabaergic Control Of the Amygdalamentioning
confidence: 99%
See 1 more Smart Citation
“…Some animal experiments have indicated that administration of GABA receptor agonists or antagonists into the amygdala can influence the concentration of GABA ( Sanders and Shekhar, 1995 ; Barbalho et al, 2009 ). These have included GABAergic agonists such as benzodiazepines ( Sigel and Lüscher, 2011 ), Zol ( Alò et al, 2015 ), muscimol ( Jasnow and Huhman, 2001 ; Liu et al, 2009 ), diazepam, and abecarnil ( Eva et al, 2004 ). GABAergic antagonists have included baclofen ( Gorsane et al, 2012 ), bicuculline ( Liu et al, 2009 ), and FG-7124 ( Eva et al, 2004 ; Lukkes et al, 2012 ).…”
Section: Gabaergic Control Of the Amygdalamentioning
confidence: 99%
“…GABAergic antagonists have included baclofen ( Gorsane et al, 2012 ), bicuculline ( Liu et al, 2009 ), and FG-7124 ( Eva et al, 2004 ; Lukkes et al, 2012 ). Benzodiazepines, Zol, diazepam, and abecarnil bind the subunits of GABA A receptors, and this binding increases the probability of ion channel opening in the presence of GABA ( Eva et al, 2004 ; Alò et al, 2015 ; Fast and McGann, 2017 ). On the other hand, baclofen competes with GABA for the same sites on GABA B receptors in the amygdala.…”
Section: Gabaergic Control Of the Amygdalamentioning
confidence: 99%
“…In addition, a number of evidences confirm the active role played by the glutamate ( l -Glu) neuroreceptor system on the pharmacological therapeutic mechanisms of antidepressants [ 9 ]. N -methyl- d -aspartate receptors (NMDARs) or α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid l -Glu receptors (AMPARs) are major targets of the various chronic depressive disorders [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Brain coronal sections (30 µm) were selected at an interval of 240 µm for ACS procedures in which an exposition period (25 min) to neutral red for the different brain sections was adapted for our animal model [14]. Briefly, sections were rinsed with distilled water, placed into dishes containing a pre-impregnating solution heated in a microwave oven at 45–50°C for 50 min, and cooled at room temperature for 3 h. Sections were then rinsed in distilled water, and after a quick rinse in acetone they were placed in an impregnating AgNO 3 solution for 50 min, followed by a 25-min fixation in a reducer solution (formalin, citric acid monohydrate, ethanol, distilled water) at a temperature range of 32–35°C.…”
Section: Methodsmentioning
confidence: 99%
“…This rodent model was chosen on the basis of its notable ability to tolerate chronic stressful conditions [12]. Specific tests were applied to evaluate different stress-associated behaviors: the elevated plus maze (EPM) test, used for evaluating psychomotor performances in hamsters [13, 14], and the hole board (HB) test, used for exploratory behaviors in rodents [15]; both tests are considered to be valid for assessing anxiolytic effects. Contextually, forced swim test (FST) was also applied, since it results to be a valuable approach for measuring antidepressant-like effects together with desperation states [16].…”
Section: Introductionmentioning
confidence: 99%